Persisting inhibition biases efficient rule inference under uncertainty - Zivi, Pierpaolo; Zigrino, Anna; Couyoumdjian, Alessandro; Ferlazzo, Fabio; Sdoia, Stefano (Frontiers in Psychology, 2024)
Task set inhibition supports optimal switching among tasks by actively suppressing the interference from recently executed competing task sets. It is typically studied in cued task-switching paradigms where there is no uncertainty about the task set or rule to prepare for on each trial. However, everyday situations are characterized by a certain level of uncertainty about which of several rules to follow in order to select the most appropriate set of actions. In these situations, rule selection provides a frame for action selection, allowing for the best prediction of the following events. While inhibition has been shown to influence the speed and the accuracy of task execution, affecting task set retrieval, preparation, or implementation in condition of task set switching, it remains uninvestigated whether it also affects rule selection under uncertainty. Using a card sorting set-shifting paradigm, we observed that participants exhibited a reduced preference for recently abandoned rules than less recently abandoned ones. Furthermore, we found that such a preference was not associated with a behavioural measure of working memory capacity. The results suggest that decision-making processes underlying rule inference and selection may be influenced by task-set inhibition, configuring as a conflict adjustment mechanism to the sequential history of rules application.